Nearpod Based Instruction in Teaching English as a Trend in Education - Chaerul Fadlan Saud; Syukur Saud2, Nur Aeni (Institute of Educational, Research, and Community Service, 2024)
Traditional learning approaches are now undergoing a transformation due to the inevitable trend of technology integration in education. One of the important innovations in this field is Nearpod, a dynamic platform that offers interactive and engaging opportunities for educators to develop English speaking skills. This study discusses the new practice of using Nearpod as a teaching tool to improve students' English speaking skills. This study uses a classroom action research method to briefly investigate the effectiveness of Nearpod. This platform has emerged as a cutting-edge development in English language teaching, providing new tools that can motivate and empower students to improve their speaking skills. This study reports the findings of the implementation of an online tool for synchronous and interactive learning, and its impact on students' activeness in intensive speaking learning. This classroom action research involved 46 students from the English Education Study Program, Makassar State University. Cycle 1 and Cycle 2 were conducted, and a survey was used to obtain data on students' views on the implementation of the Nearpod application. Data were analyzed using descriptive statistics, which showed that the experimental group showed slightly better improvements compared to the control group. In addition, low-ability students showed more significant improvements after using the program compared to their higher-ability friends. This research emphasizes the importance of integrating Nearpod into modern language learning approaches to better prepare students for success in a global environment.